A user supervised load-balancing scheduler - Flores, Sonia (1996)
In distributed systems load distnbutíon and balancing are primary functions directed to system performance improvement and user content. In order to decide where the incoming workload have to be allocated, maintaining a reasonabJe balance in the system, a number of non trivial tasks will be necessary. As a basement for further automatic system decision, this paper propose a user supervised processor allocation schedtiler and shows which information should be collected, when and how to collect and disseminate it to support the User decision.